2001
DOI: 10.1182/blood.v98.10.3074
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukemia and interferon-α: a study of complete cytogenetic responders

Abstract: Achieving a complete cytogenetic response (CCgR) is a major target in the treatment of chronic myeloid leukemia (CML) with interferon-␣ (IFN-␣), but CCgRs are rare. The mean CCgR rate is 13%, in a range of 5% to 33%. A collaborative study of 9 European Union countries has led to the collection of data on 317 patients who were first seen between 1983 and 1997 and achieved CCgRs with IFN-␣ alone or in combination with hydroxyurea. The median time to first CCgR was 19 months (95% CI, 17-21; range, 3-84 months). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
181
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(192 citation statements)
references
References 38 publications
6
181
0
5
Order By: Relevance
“…For those who achieved a CCR, the 10-year survival rate was 72% (95% confidence interval [95% CI], 62-82%), and was found to be correlated with the risk profile. 16 Patients who commenced IFNa with a high risk and achieved a CCR had significantly shorter survival. In contrast, for first-line imatinib-treated patients with CCR there was no significant difference in the overall survival noted between the Sokal risk groups after 60 months of imatinib treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For those who achieved a CCR, the 10-year survival rate was 72% (95% confidence interval [95% CI], 62-82%), and was found to be correlated with the risk profile. 16 Patients who commenced IFNa with a high risk and achieved a CCR had significantly shorter survival. In contrast, for first-line imatinib-treated patients with CCR there was no significant difference in the overall survival noted between the Sokal risk groups after 60 months of imatinib treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, even patients with good responses to IFN-a show a slow rate of recurrence and progression of their disease, despite ongoing IFN-a treatment. 16,30 The main requirement for a prolonged survival while receiving IFN-a treatment was achieving and maintaining a CCR. 16 In our study, 8 of the 23 patients had not achieved a CCR at 1.6 to 4.6 years after commencing IFN-a treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Recent data from a proof of concept study of TKI cessation (with IFN maintenance) following MMR on imatinib plus IFN demonstrated promising results. 25 In this study, imatinib therapy was stopped in 20 patients who had concomitantly been pretreated with imatinib and IFN for over 2 years.…”
Section: Towards the Path To A Curementioning
confidence: 99%
“…A potential theoretical concern is the possibility of patients developing advanced-phase CML during TFR without warning; however, abrupt progression to AP or BC has not been seen in the small groups of patients off therapy in the trials summarized here. Of note, cases of transformation to advanced disease have been described in patients following IFN cessation [41,42,56].…”
Section: Clinical Tfr Studies With Imatinibmentioning
confidence: 99%